Exploring Numeracy Literacy Skills among High Self-Efficacy Elementary Students: A Qualitative Study - Indah Etika; Kamid Kamid; Rohati Rohati (Journal of General Education and Humanities, 2026)
This study aims to explore the numeracy literacy skills of students who have high self-efficacy in solving contextual mathematics problems. This research is important because most previous research has focused more on the quantitative relationship between self-efficacy and numeracy skills. In contrast, qualitative studies that explore in depth the numeracy literacy skills of students with high self-efficacy remain limited. The study used a qualitative approach with two students who were categorised as having high self-efficacy based on validated questionnaire results. Data collection techniques include self-efficacy questionnaires, numeracy literacy tests, and in-depth interviews. The analysis focused on three indicators of numeracy literacy, namely the ability to use mathematical numbers and symbols in the context of daily life, the ability to analyse information in various data representations, and the ability to interpret the results of the analysis for decision-making. The results of the study show that students with high self-efficacy can understand problems well, apply mathematical operations appropriately, read and analyse data presented in tables and diagrams, and draw logical conclusions from the analysis. Although there was variation in the presentation of the completion steps, both subjects demonstrated adequate mastery of the concepts and strategies. These findings indicate that self-efficacy plays an important role in supporting students' numeracy literacy skills. Therefore, strengthening self-efficacy in mathematics learning needs to be considered to help students develop optimal numeracy thinking skills.